HUBUNGAN ANTARA PARITAS DENGAN KEJADIAN KANKER SERVIKS DI YAYASAN KANKER WISNUWARDHANA SURABAYA - Sisca Nida Mayrita; Nanik Handayani (Universitas Nahdlatul Ulama Surabaya, 2015)
Cervical cancer is a malignant disease attacked the female reproductive organ which is often found in women with high parity. The data obtained from Yayasan Wisnuwardhana Surabaya (Cancer Foundation) in 2012 showed that among 9630 women having Pap Smear, 88 (0.9%) were detected with cervical cancer. Therefore, the purpose of this study was to find out the correlation between parity and incidence of cervical cancer in the above mentioned cancer foundation.The design of study was analytic-observational done by applying cross sectional approach. The population involved 400 women having Pap Smear in the stated cancer foundation in March 2014. 200 respondents were chosen as the samples by using probability sampling, in which simple random sampling technique was used in this study. The instrument for collecting the data was the medical record. The data were then analyzed by using Chi-Square statistic test with the significance level α = 0.05. The result of study showed that none of the nullipara and primipara (0%) suffered from cervical cancer, whereas few of the multipara (5.9%) and half of the grandemultipara (50%) suffered from cervical cancer. Moreover, the result of Chi-Square was not qualified so that Fischer’s Exact test was used and showed that p = 0.000 < α = 0.05 so that H0 was rejected illustrating that there was a correlation between parity and incidence of cervical cancer in the above mentioned cancer foundation.In conclusion, the higher parity, the more risk for cervical cancer. The facility of health services are expected to give more health counseling to the women with high risk of having cervical cancer to have Pap Smear.